C-phycocyanin from Arthrospira maxima LJGR1: production, extraction and protection - Antonio, Emma (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2016)
C-phycocyanin (C-PC) overproduced by Arthrospira maxima LJGR1 under high urea and salt concentrations was extracted by different methods and evaluated as an antioxidant activity. A. maxima was grown in flat plate photobioreactors, using modified Zarrouk medium with 624 mg L-1 urea and 15 g L-1 NaCl to produce 11 mg C-PC L-1d-1. Agitation, sonication at 35 and 45°C and enzymatic lysis of the cell wall were tried. The C-PC yields, purity and inhibition of the oxidant radicals (DPPH & ABTS) obtained by the best extraction methods were 215 mg C-PC g-1, 0.74, 92% and 29%; when agitation and 221, 0.75, 87% and 27% using sonication at 45°C. Chia mucilage and amaranth flour coatings best preserved C-PC antioxidant activity from temperature variations and up to six days shelf life at 20°C. An activation energy of 160 kJ mol-1 has been obtained with chia mucilage, and the least color degradation rate (râˆ†E*) of 4.2 d-1 with amaranth flour.